EXPLORING THE INTERACTION EQUATION: VALIDATING A RUBRIC TO ASSESS AND ENCOURAGE INTERACTION IN DISTANCE COURSES - Roblyer, Margaret D.; Wiencke, William R. (Online Learning, 2004)
The degree of interaction among participants in distance courses is widely acknowledged to be an indicator of successful learning experiences; interaction has been found to contribute to both achievement and student satisfaction. As an increasing number of distance courses move to a completely asynchronous, online format, providing for better interaction is an important means of assuring course quality. To allow measurement and study of interaction in online courses, five elements were identified that contribute to interaction, and a rubric was designed to assess the degree of each in distance courses [1]. A previous use of the rubric in one online class [1] indicated the instrument had good convergent and divergent validity and reliability in terms of consistency of results across students. The current study focused on establishing the rubric’s concurrent validity and consistency of results across four distance courses. Recommendations are made to increase the usefulness and reliability of the rubric in practice.